(untitled) - McCarthy, Michael; Michael McCarthy; Felicity O'Dell (Cambridge,New York, 2002)
The fourth in the family of best-selling vocabulary reference and practice books from elementary to advanced level. The perfect choice for advanced-level students wanting to build their vocabulary skills. English Vocabulary in Use: Advanced includes over 2,000 new words and expressions which are presented and practised in typical contexts appropriate to this level. The book is informed by the Cambridge International Corpus to ensure that the vocabulary selected is useful and up-to-date
Keywords: Vocabulary; English language; English language